Peran Orang Tua Dalam Proses Penyesuaian Diri Anak Usia Dini Terhadap Kegiatan Pembelajaran Di Rumah - Desi Okta Sari; Risky Drupadi; Ulwan Syafrudin (Universitas Muhammadiyah Surabaya, 2021)
The role of parents is very much needed during the process of learning activities for children at home, namely providing education to their children so that they understand about the current pandemic. This research was conducted with the aim of knowing the role of parents in the process of adapting to early childhood learning activities at home. The research method used is qualitative with a case study approach. Data collection through interviews and observations. Data analysis techniques consisted of data reduction, data presentation, and drawing conclusions. The results of this study indicate that parents play a role in the application of learning at home during the pandemic in educating children including mentoring and as a motivator. Therefore, it can be said that the role of parents in children's adjustment needs to be improved so that children can be more optimal in participating in learning activities at home.